2008
DOI: 10.1080/07853890701779586
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin‐2 levels as a biomarker of cardiovascular risk in patients with hypertension

Abstract: Among patients with hypertension, raised levels of Ang-2 were predictive of MI, and further study is warranted to evaluate the use of this biomarker in CVD management, risk stratification, and prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 27 publications
3
41
0
Order By: Relevance
“…Lee et al [18] demonstrated that angiopoietin-1 prevents hypertension and target organ damage. Furthermore, elevated angiopoietin-2 levels have been described as biomarkers of cardiovascular risk in patients with hypertension [19].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [18] demonstrated that angiopoietin-1 prevents hypertension and target organ damage. Furthermore, elevated angiopoietin-2 levels have been described as biomarkers of cardiovascular risk in patients with hypertension [19].…”
Section: Discussionmentioning
confidence: 99%
“…Although we still do not know whether elevated angiopoietin-2 levels are a cause or an effect of ACS and hypertension, increased angiopoietin-2 levels have been reported as a biomarker of cardiovascular risk (myocardial infarction, stroke and death) in patients with hypertension [25]. We, therefore, hypothesized that genetic variants of ANGPT2 (the gene encoding angiopoietin-2) would contribute to the susceptibility of stroke.…”
Section: Introductionmentioning
confidence: 98%
“…15 We set up the hypothesis that, under conditions where RAAS is not only caused by RAAS (+) itself but also because of peripheral vascular disorders, intra-renal ischemia would increase, tubulointerstitial disorder has progressed, the level of eGFR would drop, and CVREs would increase as a result. In this longitudinal study, we clarified that RAAS (+) and a decline in eGFR are both independent risk factors for CVREs in diabetes mellitus patients; the latter being more powerful than the former.…”
Section: Discussionmentioning
confidence: 99%